Price Discovery and Volatility Spillover for Indian Energy Futures Market in the Pre- and Post-Crisis Periods - Seth, Neha; Sidhu, Arpit (Indian Journal of Finance, 2021)
The present paper examined the price discovery and volatility spillovers in pre and post-crisis (global financial crisis and European sovereign debt crisis) periods of spot and futures energy markets in India from January 1, 2007 – December 31, 2018, with the help of closing price series listed on the Multi Commodity Exchange Limited (MCX) for both spot and futures crude oil and natural gas markets. The data were examined using Johansen cointegration test, vector error correction (VEC) model, autoregressive distributed lag (ARDL) model, and Glosten-Jagannathan-Runkle generalized autoregressive conditional heteroscedasticity (GJR-GARCH) model to measure the price discovery and volatility spillovers. For price discovery, most of the sample cases had a long-run equilibrium relationship between their spot and futures prices, and the futures (spot) market led the spot (futures) market in the long-run in most sample periods (post-ESDC period). In case of volatility spillover, most of the results concluded the dominance of the futures market over the spot market except crude oil in the post-ESDC period. All these factors made the futures market more efficient and cost-competitive in terms of price discovery. So, it can be concluded that the market participants may depend on the futures market’s price changes for their investment and trading decisions. The results of during and post-crisis periods may be helpful for the current investors for modification of their optimum portfolio. Investors and policy makers may draw meaningful conclusions and become prepared for the next crisis period.